Tomato Brown Rugose Fruit Virus Nextstrain Build Version 4: Pathways of Introduction and Local Spread - Pier P. M. de Koning; Aimee R. Fowkes; Zafeiro Zisi; Despoina Beris; Carla Oplaat; Sam McGreig; Anna Skelton; Ian P. Adams; Jerom van Gemert; Christel de Krom; Michael Visser; Marcel Westenberg; et al. (PhytoFrontiers)
Tomato brown rugose fruit virus (ToBRFV; Tobamovirus fructirugosum) is a harmful virus significantly reducing yield and fruit quality in tomato. It was first detected in Israel and Jordan in 2015 and quickly reached a near-global distribution. Following the outbreak of ToBRFV in the Netherlands in 2019, the Dutch National Plant Protection Organization (NPPO-NL) created a Nextstrain build, which was updated in 2021 and 2023. Here, we announce the release of 82 new (near) complete ToBRFV genomes with associated metadata and the fourth version of the ToBRFV Nextstrain build, which has expanded from 179 to 336 (near) complete genomes. This ToBRFV Nextstrain build is a powerful tool for gaining more insight into the epidemiology of ToBRFV, i.e., on pathways of introduction and the spread and possible origin of the rapidly emerging clade 7 sequence type isolates. The ToBRFV Nextstrain build is available at https://nextstrain.nrcnvwa.nl/ToBRFV/20240205. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.